Reforming family taxation in Germany: Labor supply vs. insurance effects - Hans Fehr; Manuel Kallweit; Fabian Kindermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The present paper quantifies the economic consequences of eliminating the system of income splitting in Germany. We apply a dynamic simulation model with overlapping generations where single and married agents have to decide on labor supply and homework facing income and lifespan risk. The numerical exercise computes the resulting welfare changes across households and isolates aggregate efficiency effects of a move towards either individual taxation or family splitting. Our results indicate strongly that a switch towards individual taxation performs best in terms of economic efficiency due to reduced labor market distortions and improved insurance provision. In our benchmark calibration the efficiency gain amounts to roughly 0.4 percent of aggregate resources. Excluding home production significantly reduces aggregate efficiency gains while including marital risk slightly improves the efficiency of individual taxation.
Keywords: H21; H24; J12; J22; 330; stochastic general equilibrium; home production; female labor supply; tax unit choice; insurance provision